Analysis of the Application Activity-Based Costing Cost of Production Bens Qurban - Putri, Desmahan Anugrah; Hurriyaturrohman, Hurriyaturrohman; Rumiasih, N. A. (inovator, 2024)
Cost of Production or product cost is an important element to assess the success (performance) of a trading or manufacturing company. Cost of production is related to indicators of the company’s success, such as gross sales profit, net profit. The calculation of cost of productions (COP) is all production costs used to process a raw material into goods.to process a raw material into finished goods in a certain period of time. The research focused on the products BENS QURBAN Delivery, Titip Sembelih and Praktis. The research begins with an exploration of what activities will affect the occurrence of production costs charged to these products. In this study, the main focus of research is to analyze the object of research by making descriptions and grouping them into categories of costs and activities in more detail in determining the cost of production. The determination of cost drivers for each activity determines the accuracy of factory overhead costing. COP calculation with ABC method results in overcosting conditions for BENS QURBAN delivery products and under costing for BENS QURBAN Titip Sembelih and Praktis compared to hpp with traditional methods because the Activity Based Costing (ABC) method charges activities and activity costs in more detail for each product.